파킨슨병 환자에 대한 집단 음악요법의 심리적 중재 효과 - 배은숙(Eunsook Bae); 김미정(Mijung Kim) (지역사회간호학회지, 2016)
Purpose: Music therapy is a non-pharmacological treatment of the behavioral and psychological symptoms. This study was conducted to contribute to the rehabilitation of patients with idiopathic Parkinson's disease in the areas of functionality, emotionality and sociability. Methods: The study included 35 participants, aged between 52 and 77 years, who were diagnosed with idiopathic Parkinson's disease (IPD) and reported suffering from depression, chronic illness anticipated stigma, and worrying about quality of life. The patients were recruited from the department of outpatient neurology at School of Medicine, D University in B Metropolitan City. Group music therapy was performed for nine weeks. The results were analyzed by repeated measures ANOVA. Results: In terms of stigma, there were significant differences between two groups and time (p<.05). Analysis of the interaction between time and service method revealed significant differences (p<.05). Between time, and the interaction between time and service method revealed significant differences in terms of quality of life (p<.05). Conclusion: The results suggest that group music therapy will be effective on the psychosocial well-being of patients with Parkinson's disease living in assisted and independent living communities.